2014
DOI: 10.1080/10826076.2014.936606
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Purification of Two Minor Compounds from Radix isatidis by Integrative MPLC and HSCCC with Preparative HPLC

Abstract: Radix isatidis has been widely used as a Chinese traditional medicine for its anti-virus and anticancer activities where the minor components may contribute to these beneficial pharmaceutical effects. In order to enrich the target minor compounds effectively and rapidly, extraction, medium-pressure liquid chromatography (MPLC), high-speed countercurrent chromatography (HSCCC) and preparative high-performance liquid chromatography (pre-HPLC) were integratively used for separation and purification of two target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Moreover, all UV spectra with their λmax at approximately 270 and 330 nm of peaks 1–4 agree with flavonoid characterization [ 25 ]. Based on the ESI-MS/MS and literature data, peaks 1–4 were assigned as isovitexin, isovitexin-3″-O-glucopyranoside, isoscoparin, and isoscoparin-3″-O-glucopyranoside ( Figure 3 ) [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, all UV spectra with their λmax at approximately 270 and 330 nm of peaks 1–4 agree with flavonoid characterization [ 25 ]. Based on the ESI-MS/MS and literature data, peaks 1–4 were assigned as isovitexin, isovitexin-3″-O-glucopyranoside, isoscoparin, and isoscoparin-3″-O-glucopyranoside ( Figure 3 ) [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some previously developed analytical methods to control the Isatidis Folium quality are thin-layer chromatography, high-performance liquid chromatography-ultraviolet (HPLC-UV), HPLC-atmospheric pressure chemical ionization (APCI)-mass spectrometry (MS), HPLC-electrospray ionization (ESI)-MS, nuclear magnetic resonance, and Fourier Transform (FT)-Raman spectroscopy [ 16 , 17 , 18 , 19 ]. However, none of these established methods can be used to identify and quantify the bioactive compounds in our enriched Isatidis Folium extract because of many components with a high amount in the crude extract (such as alkaloids and glycosides) were removed during the purification process.…”
Section: Introductionmentioning
confidence: 99%
“…Although some authors have reported high purities (>90%) using HSCCC , this type of separations frequently require a pre‐separation step employing macroporous resins when the crude extracts are complex . In addition, HPLC is orthogonal and complementary to HSCCC, and can often provide straightforward resolution of otherwise difficult separations by HSCCC . However, when considering these comparisons it should be noted that there is room for further optimization of both methodologies, in terms of both throughput and efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, its merits of low cost, high sample loading, high efficiency, and various available modes [12,13] makes it suitable for the separation of minor components. Seven studies on the separation of minor compounds from natural products by HSCCC have been conducted over the last 5 years [14][15][16][17][18][19][20]. For compounds with similar polarities, it is sometimes not easy to find a perfect solvent system that performs at high purity in a one-step separation by HSCCC due to limitations in theoretical plates.…”
Section: Introductionmentioning
confidence: 99%